The Presence and Distribution of Elastin in the Posterior and Retrobulbar Regions of the Mouse Eye - Gelman, Scott (2009)
The Presence and distribution of elastin in the posterior and retrobulbar regions of the mouse eye was investigated. Mice of two strains (C57/BL6 and DBA/2J) were studied at 2 months and 8-12 months of age. Light, confocal, and transmission electron microscopy were used to identify elastin, using immunohistochemical techniques and ultrastructural evaluation. Elastin was found in the following ocular structures: conjunctiva, muscle tendons, sclera, choroid, and meninges. The elastin in the sclera was most dense in a ring surrounding the peripapillary optic nerve head, with its presence in the inner sclera declining with greater distance from the nerve head. Elastin fibers were oriented in the sclera along what would be expected to be the principal stress directions generated from the intraocular pressure, though actual biomechanical measurements have not yet been made in the mouse sclera. Elastin comprises a portion of the mouse sclera and its distribution in the peripapillary area is similar to that in human eyes.